The Effect of Motivation and Compensation on Employee Performance PT. Kebab Turki Baba Rafi Surabaya Branch with Work Satisfaction as an Intervening Variable - Ghufroni Ghufroni; I Nyoman Sudapet; Hamzah Denny Subagyo (LPPM NAROTAMA UNIVERSITY, Indonesia, 2019)
The purpose of this study is 1. To analyze the effect of motivation on employee satisfaction at PT. Kebab Turki Baba Rafi Surabaya branch 2. To analyze the effect of motivation on employee performance at PT. Kebab Turki Baba Rafi Surabaya branch3. To analyze the effect of compensation on employee satisfaction at PT. Kebab Turki Baba Rafi Surabaya branch 4. To analyze the effect of compensation on employee performance at PT. Kebab Turki Baba Rafi Surabaya branch 5. To analyze the influence of employee satisfaction on employee performance at PT. Kaba Turki Baba Rafi branch of Surabaya. This research is quantitative research. The population and samples were distributed by 58 respondents. Data collection techniques using a questionnaire. Analysis of the data used is Convergent Validity, Discriminant Validity, Reliability and Average Variance Extracted (AVE). The results showed the effect of the Motivation variable (X1) on Employee Satisfaction (Y1) was significant at 0.002. And Motivation (X1) is not significant with Employee Performance variable (Y2) of 0.297 which means negative. based on the correlation for the Compensation variable (X2) on Employee Satisfaction (Y1) of 0.880 which means negative. And for the Compensation variable (X2) on Employee Performance (Y2) of 0.691 which means negative. And for the Employee Satisfaction variable (Y1) on Employee Performance (Y2) of 0.009 which means strong. The results of this study indicate that, Motivation has a significant effect on employee satisfaction, which leads to employee performance. And employee satisfaction has a significant effect on employee performance.